The Characteristics of Fish Diversity and Age Structure in Pelus River Area Residency of Banyumas - Indonesia - Susanto Susanto; Muhammad Azharul Rijal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2021)
This research was purposed to reveal and discover fish community in Pelus River, Banyumas Residency. It includes: (1) water quality which include physical and chemical parameters and plankton species variation, (2) Fish diversity, (3) Fish age structure was based weight and total length. Research done by survey methods, with purposive random sampling methode. The research was conducted in Pelus River Region of Banyumas Residency, which were location one (upstream of Pelus River), location two (middlestream of Pelus River), and location three (downstream of Pelus River). This Research applied survey method, with purposive random sampling technique. Research was done in eight months which replicated every month, since December 2016 untill May 2017. Result indicated that nesearch fishes caught were as many as 544 fishes divided to 18 Species, eight Family and five Ordo. Water quality factor including aquatic physical and chemical parameters, which were temperature, flowrate, clarity, dissolved oxygen and pH and bilogical parameter (plankton) variation in Pelus River Banyumas Residency were in good condition and suitable for fish life. Cyprinidae Family found as most variated species and most founded spesies in individual number at Pelus River Banyumas Residency. There were low species diversity, but there weren’t found any dominancies. Fish species diversity in Pelus river low. Age structure shows the condition of fish in Pelus River of Banyumas regency is in a vulnerable condition, so it needs attention in order to conserve fish species. Keywords: Fish diversity, age structure, Pelus river, Banyumas